Role of fibroblast growth factor receptor signaling in kidney development - Bates, Carlton M. (2011)
Fibroblast growth factor receptors (Fgfrs) are expressed throughout the developing kidney. Several early studies have shown that exogenous fibroblast growth factors (Fgfs) affect growth and maturation of the metanephric mesenchyme (MM) and ureteric bud (UB). Transgenic mice that overexpress a dominant negative receptor isoform develop renal aplasia/severe dysplasia, confirming the importance of Fgfrs in renal development. Furthermore, global deletion of Fgf7, Fgf10, and Fgfr2IIIb (isoform that binds Fgf7 and Fgf10) in mice leads to small kidneys with fewer collecting ducts and nephrons. Deletion of Fgfrl1, a receptor lacking intracellular signaling domains, causes severe renal dysgenesis. Conditional targeting of Fgf8 from the MM interrupts nephron formation. Deletion of Fgfr2 from the UB results in severe ureteric branching and stromal mesenchymal defects, although loss of Frs2α (major signaling adapter for Fgfrs) in the UB causes only mild renal hypoplasia. Deletion of both Fgfr1 and Fgfr2 in the MM results in renal aplasia with defects in MM formation and initial UB elongation and branching. Loss of Fgfr2 in the MM leads to many renal and urinary tract anomalies as well as vesicoureteral reflux. Thus, Fgfr signaling is critical for patterning of virtually all renal lineages at early and later stages of development.